The sexual lifestyles of gay and bisexual men in England and Wales - Weatherburn, Peter; Hunt, Andew J.; Hickson, Ford; Davies, Peter M. (London : Project Sigma, 1992)
Fonds Suzan Daniel (FSD)
Engels
Brochure